Spitzoid melanoma of childhood: a case series and review. (May 2015) - Batra, Sandeep
SUMMARY : Spitzoid melanomas (SM) and atypical Spitz tumors (AST) are rare pediatric neoplasms. We performed a retrospective, single-institution review and report our institutional experience. We identified 10 patients (median age: 12.5 years). A sentinel node biopsy (SNB) was performed in 8/10 (80%) patients, and interestingly 7/8 (87.5%) were found to be positive for malignant cells. A complete regional lymphadenectomy was performed in all SNB-positive patients, but only 2/8 (25%) were found to have additional lymph node spread. Adjuvant therapy was administered in 5/8 SLNB-positive and 2/2 (100%) regional LN-positive cases. All patients had excellent long-term outcomes (100% survival). This report highlights the excellent outcomes associated with SNB + pediatric SM and AST.